Pool Fire Suppression Using CO2 Hydrate; Energies; Vol. 15, iss. 24 - Gaydukova O. S. Olga Sergeevna; Misyura S. Ya. Sergey Yakovlevich; Donskoy I. G. Igor Gennadjevich; Volkov R. S. Roman Sergeevich; Morozov V. S. Vladimir Sergeevich (2022, 2022)
Title screen